A Retinol Isotope Dilution Equation Predicts Both Group and Individual Total Body Vitamin A Stores in Adults Based on Data from an Early Postdosing Blood Sample. Issue 10 (10th August 2016) - Green, Michael H; Ford, Jennifer Lynn; Green, Joanne Balmer; Berry, Philip; Boddy, Alan V; Oxley, Anthony; Lietz, Georg
Abstract: Background: Retinol isotope dilution (RID) is used to determine vitamin A total body stores (TBS) after an oral dose of a vitamin A stable isotope. The generally accepted prediction equation proposed by Olson's group in 1989 (Furr et al. Am J Clin Nutr 1989;49:713–6) includes factors related to dose absorption and retention, isotope equilibration in plasma compared with stores, catabolism during the mixing period, and the optimal time for measuring plasma isotope enrichment. Objectives: The objectives were 1 ) to develop a modified RID equation and identify an earlier sampling time for predicting TBS and 2 ) to improve prediction in individuals as well as groups. Methods: To develop a modified RID equation, we used results of model-based compartmental analysis [the Simulation, Analysis and Modeling software (WinSAAM version 3.0.8; http://www.WinSAAM.org )] of plasma [ 13 C10 ]retinol kinetic data from 32 previously studied, healthy young adults of European ancestry who had moderate vitamin A intakes and who ingested 2.95 μmol [ 13 C10 ]retinyl acetate. Results: We examined the time dependence of factors in the prediction equation related to absorption/retention ( Fa ) and isotope equilibration ( S ) and determined that 4 or 5 d postdosing was the optimal sampling time. TBS calculated by the equation TBS = Fa x S x (1/SAp ), where SAp is plasma retinol specific activity (fraction of dose/μmol), were highly correlated with model-predicted TBS ( r = 0.95 and 0.96 for 4 and 5 d, respectively; P < 0.001); predictions for individuals were also highly correlated ( R s = 0.94 and 0.94; P < 0.001). Conclusion: The equation TBS ≈ 0.5 × (1/SAp ) accurately predicted vitamin A TBS in this group of 32 healthy young adults and its individual members with the use of data from 1 blood sample taken 4 d after isotope administration.